Structure analysis of sixand eight-link walking mechanisms - Korendiy, Vitaliy; Skripnik, Roman; Khomych, Ihor (Lviv Polytechnic Publishing House, 2016)
Structure analysis of six- and eight-link walking mechanisms is carried out. Structure formulas of corresponding mechanisms are formed. The recommendations for further kinematic analysis method selection are presented.
Keywords: structure analysis; walking mechanism; degree of freedom; kinematic analysis; structure formula; drive; mover